2014
DOI: 10.1523/jneurosci.4367-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Dynamics in the Orofacial Sensorimotor Cortex during Motor Skill Acquisition

Abstract: The orofacial sensorimotor cortex is known to play a role in motor learning. However, how motor learning changes the dynamics of neuronal activity and whether these changes differ between orofacial primary motor (MIo) and somatosensory (SIo) cortices remain unknown. To address these questions, we used chronically implanted microelectrode arrays to track learning-induced changes in the activity of simultaneously recorded neurons in MIo and SIo as two naive monkeys (Macaca mulatta) were trained in a novel tongue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 69 publications
6
43
0
Order By: Relevance
“…Similar patterns were observed for the mean MS coherence across neuronal pairs with significant modulation of coherence (Fig. 2D, shuffle test, P < 0.01), consistent with the task modulation of theta coherence previously found within MIo and within SIo (16). Out of all of the possible combinations of paired signals (n = 44,152) from 10 datasets, the proportion of neuronal pairs that showed significant task modulation of MS coherence (i.e., "functional network") was highest in theta and was significantly lower in the higher frequency bands (Fig.…”
Section: Frequency-specific Modulation Of Spike-spike Coherence (Ms) supporting
confidence: 89%
See 3 more Smart Citations
“…Similar patterns were observed for the mean MS coherence across neuronal pairs with significant modulation of coherence (Fig. 2D, shuffle test, P < 0.01), consistent with the task modulation of theta coherence previously found within MIo and within SIo (16). Out of all of the possible combinations of paired signals (n = 44,152) from 10 datasets, the proportion of neuronal pairs that showed significant task modulation of MS coherence (i.e., "functional network") was highest in theta and was significantly lower in the higher frequency bands (Fig.…”
Section: Frequency-specific Modulation Of Spike-spike Coherence (Ms) supporting
confidence: 89%
“…To investigate cortico-cortical interactions between these areas, we measured coherence of spiking and local field potentials (LFPs) recorded simultaneously from MIo and SIo of the left hemisphere as monkeys learned a simple and controlled tongue protrusion task. Several studies using this behavioral paradigm have reported neuroplasticity and modulation of neuronal activity related to tongue protrusion separately in MIo and SIo (13)(14)(15)(16)(17). Here, we show that interactions between MIo and SIo involve coherent networks at multiple frequencies.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…2B. These changes in neuronal recordings, based on characteristics of the extracellular recordings over weeks of time, are consistent with other examinations of the recording stability (Arce-McShane et al 2014;Dickey et al 2009). …”
Section: A B C D Esupporting
confidence: 87%